EFEKTIVITAS PEMBELAJARAN DISCOVERY LEARNING BERBASIS DIGITAL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK - Siti Khodijah; Herpratiwi Herpratiwi; Helmy Fitriawan (LPPM Institut Pendidikan Nusantara Global, 2023)
Along with advances in science and technology, educational institutions are required to play an active role in improving the quality and quality of education optimally to balance advances in science and technology as well as increase the competitiveness of graduates to face intense competition and challenges in the world of work. Based on the results of initial observations of learning at SDN 1 Rawalaut, the learning process is still monotonous using only blackboards, printed books, and worksheets as learning media. Learning that tends to be monotonous certainly has a very significant effect on the development of student learning in the classroom which causes student learning outcomes to decrease. This study aims to determine the effectiveness of digital-based Discovery Learning learning to improve mathematics learning outcomes for students at SDN 1 Rawalaut. The method used in this study is the SLR (Systematic Literature Review) method. Data collection is carried out using documentation and reviewing all articles related to the discovery learning model. Based on the results of the research been carried out in the table of research results, explains that the effectiveness of learning media contributes to the teaching and learning process in the classroom, with the presence of digital media, of course, learning can be creative and fun and of course can improve student learning outcomes, especially at SDN 1 Rawalaut.